Problems of Proving and Confiscating Crypto Assets Proceeding from Money Laundering Crimes by the Prosecutor's Office in the Indonesian Criminal Justice System - Emil Brunner; Lucky Ferdiles (Journal Customary Law, 2026)
This study aims to analyze the challenges of proving and confiscating crypto assets in money laundering crimes and to formulate an adaptive legal concept within the Indonesian criminal justice system. The method used is normative juridical with a statutory and conceptual approach, through a review of the Criminal Procedure Code and its updates, Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, and Law Number 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions (ITE) Law. The results show that the Indonesian criminal law evidentiary system is not yet completely able to accommodate the decentralized, pseudonymous, and cross-jurisdictional characteristics of crypto assets, resulting in difficulties in identifying ownership, validating blockchain evidence, and relying on expert testimony. Furthermore, the mechanism for confiscation and confiscation of assets is also ineffective due to limited regulations regarding private key control, digital evidence management, and technical and jurisdictional barriers. Therefore, legal reform is needed by strengthening blockchain-based electronic evidence regulations, developing adaptive asset recovery mechanisms, including non-conviction-based forfeiture, and enhancing the institutional capacity of the Attorney General's Office and international cooperation. This will enable a criminal justice system that is responsive to technological developments and effective in combating crypto-asset-based money laundering.